2012
DOI: 10.2334/josnusd.54.85
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral mucosal disorders in institutionalized and non-institutionalized psychiatric patients: a study from AVBR Hospital in central India

Abstract: Dental treatment is reported to be the greatest unattended health need of people with a disability. The aim of the present study was therefore to quantify the prevalence of oral diseases with a psychosomatic component (recurrent aphthous stomatitis, burning mouth syndrome, and oral lichen planus) in psychiatric patients and to screen these patients for any other oral disorders, so that better care could be provided. In this cross-sectional, singleassessment study, 150 psychiatric patients were evaluated for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 20 publications
1
23
0
4
Order By: Relevance
“…As shown in Table 1, the reported prevalence rates of BMS differ widely, from 1.0% to 40%. 1,5,2231 Most studies report a prevalence of about 1% to 6%, with a significantly higher prevalence in women. Our study is suggestive that BMS is an uncommon disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 1, the reported prevalence rates of BMS differ widely, from 1.0% to 40%. 1,5,2231 Most studies report a prevalence of about 1% to 6%, with a significantly higher prevalence in women. Our study is suggestive that BMS is an uncommon disease.…”
Section: Discussionmentioning
confidence: 99%
“…39 In addition, the use of diverse study methods in earlier studies—including surveys, questionnaires, and retrospective reviews—influences results and complicates comparison. 5,22,23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important in patients with special needs, such as psychiatric patients (1). These patients have a tendency to be more prone to develop bucco-dental diseases, due to their lack of motivation, the difficulty to perform a proper mouth health technique, the hurdles that have to be overcome to treat them dentally, and the negative effects caused by psychotropic medications, affecting the normal physiology of salivary glands and epithelia of the oral mucous, causing xerostomy or sialorrhea (3-5).…”
Section: Introductionmentioning
confidence: 99%
“…Different authors have reported that patients with mental illnesses get inadequate dental care due to ignorance, fear, stigmas, or negative attitudes by the professionals (1). …”
Section: Introductionmentioning
confidence: 99%